RHYME VARIATIONS OF MALAY PANTUN - Purwanto, Wachid Eko (Jurnal Tradisi Lisan Nusantara, 2024)
Basically, the rhyme has a fixed and unchanging standard form. Pantun is an old type of poetry that is bound by abab rhymes, the number of 8-12 syllables per line, the number of 4 lines per stanza, 2 sampiran lines, and 2 content lines. The fixed form of the rhyme turns out to have variations. This study aims to describe the variations of rhyme writing in the anthology of Pantun Melayu published by Balai Pustaka. The research method uses content analysis. The results showed that there were variations in the number of lines, which resulted in variations in rhyme. The variation in the number of lines shows that there are 4 kinds of rhyme variants, namely 6-line rhyme, 8-line rhyme, 10-line rhyme, and 14-line rhyme. This variation in the number of lines gives rise to new variations of rhyme. The variations of the new rhymes are as follows: The 6-line rhyme has two rhymes, abc abc and aba aba. The 8-line rhyme has two rhymes, abcd abcd and abcb abcb. The 10-line rhyme has two rhymes: abcaa abcaa and abcde abcde. The 14-line rhyme has a rhyme abacdef abacdef.